Rede de apoio à escolarização inclusiva na educação básica: dos limites às possibilidades - Calheiros, David dos Santos (2019)
Special Education literature currently recommends the setting up of support networks for school inclusion, to guarantee the right to education and to promote the construction of inclusive schools for people with disabilities. A network of support for school inclusion is understood as being a group of organizations, entities or professionals that provide synchronized services, in collaboration with educators, with the aim of supporting the schooling of the target public students of Special Education (PAEE) in common classes. In the Brazilian educational policy, Special Education student enrollment is guaranteed in the common school, but the support offered is still simplistic and inadequate, the most frequent being extracurricular Specialized Educational Attendance. The result has been that families have preferred to keep their children in specialized institutions or associate attendance at common schools with that of special educational services in special schools due to the possibility of having access to a network with more support. The fact is that this scenario maximizes the weakening of the school inclusion policy, while strengthening the outsourcing of the support system and of specialized institutions, while at the same time it releases the public school from the responsibility of providing for the distinct needs of its students. Thus, faced with a reality of the existing support system in Brazilian public schools, the question that gave rise to the present study was how to establish a network to support school inclusion by articulating public education, considering the intersectoriality only as a complementary arrangement. The aim of the research was to analyze the development and implementation processes and the possibilities and limits of support network services for the school inclusion of students with cerebral palsy, which was the condition selected due to requiring a variety of support services. This is an action research based on a qualitative approach, and presents the case of a student in transition between two municipal public schools in Maceió, the state of Alagoas, Brazil (the former refers to early education and the latter to primary school - 1st year). A total of 19 people among them directors; coordinators; teachers of special classes; a special education teacher; a support professional; a special education technician from the municipal network; professionals from a Specialized Center in Rehabilitation; a representative of the Nucleus of Studies in Education and Diversity (NEEDI), the student with cerebral palsy and his guardian; and the researcher; all of whom were part of the support network and who voluntarily participated in the study, which was based on an intentional non-probabilistic sample. Data were collected by means of: a questionnaire; focus group and interview scripts; registers of conversation circles; documentary analysis; and a field journal. Despite defining the themes based on the researcher’s theoretical interest or on a preexisting coding framework, the data corpus was supported by thematic analysis and was data-oriented (inductive approach). After synthesis, six themes developed, henceforth called assumptions for the setting up of the support network for school inclusion within the reality investigated, and were as follows: 1) Understanding of the scenario of Special Education and identification of support services; 2) Agreement with management and partners; 3) Composition of members and definition of roles; 4) School participation and identification of support needs; 5) Planned and implemented actions; 6) Evaluation. The results obtained prove the thesis that an educational policy of school inclusion, aimed at guaranteeing the right to education of the PAEE students, within Brazilian reality, requires the implementation of a diversified support network. Researching contexts that already have diversified services, so as to study the network operation, is suggested for future studies, in order to evaluate the level of articulation and how to improve it, and also to investigate how the composition of this network should be, based on the professionals involved to make schools more inclusive for all, especially for PAEE students whose barriers seem to be more established.